OPTIMALISASI WAKAF PRODUKTIF SEBAGAI UPAYA PEMBANGUNAN DAN PEMBERDAYAAN EKONOMI MELALUI WISATA LOKAL - Aliful Muhlis; Faridatur Rosyidah; Mohammad Zainuri (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2021)
ABSTRAK Introduction: Waqf has a strategic economic dimension in empowering and increasing economic productivity if managed properly and with incentives. Productive waqf is a scheme for managing waqf donations from the people, namely by making these donations productive so that they are able to produce a sustainable surplus. Methods: This study uses a qualitative research method with a descriptive approach. The type of data used is secondary data. The techniques used in data collection in this research include literature study, documentary, discussion, and intuitive-subjective. Result: Tourism is one of the important assets to help support the economy of a country. Each country continues to try to take advantage of the existing potential to attract tourists to visit their country. So that tourism can contribute a lot in Indonesia in various fields, especially in the economic field. However, there are several tourist destinations that have not been managed properly due to the lack of funds to support these facilities, so it is necessary to optimize funds to provide concrete solutions in increasing tourism potential so that community economic empowerment is increasing. So that the existence of productive waqf can be an opportunity for optimizing tourism in order to achieve economic empowerment. Conclusions and suggestions: Optimizing productive waqf aims to empower the people's economy. Where productive waqf can assist in the development of coastal tourism by optimizing facilities that can attract visitors so that with the existence of productive waqf it is expected to be able to support sustainable development in the tourism sector so as to reduce economic problems that often occur in the community, such as lack of employment and poverty. . Keywords: productive waqf, economic empowerment, tourism.